Desain Bilik Sterilisasi "White Box" - Noor Hamidah; Dwi Anung Nindito; Tatau Wijaya Garib; Waluyo Nuswantoro; Mahdi Santoso (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2021)
ABSTRACT The sterilization chamber is designed to sterilize the body using a filler formulation that is not harmful to the skin surface. Formulation, namely the composition of filler fluids (type, dose and amount) using substances that are safe for the body accordingly, certainly provides benefits. The use of the sterilization booth uses the correct and safe filling fluid. The sterilization chamber uses a mist nozzle sprayer (with the appropriate discharge) to spray the filling liquid so that the user is safe. This sterilization booth is named "White Box". This "White Box" research aims to design (functional and structural) and test (function test and performance test) on a system and mechanism for condensing the condensation of a humidifier that can fill the sterilization room optimally. The design method of the "White Box" sterilization booth uses a qualitative method with the following phases: (1) The preparation stage, namely the functional design and the structural design of the "White Box"; (2) The implementation stage is analyzing the use of tools and materials and making sterilization booths; (3) Post-implementation stage, namely testing the sterilization chamber, including the function test and performance test of the sterilization chamber. The design activity of the "White Box" sterilization booth was carried out by testing various variations of the prototype, including variations in the dimensions of the distribution pipe, the shape of the distribution pipe, and variations of the piping system. The validation process includes: (1) The diameter of the pipe against humidifier dew bursts; (2) The shape of the piping against humidifier dew spray; and (3) the length of the pipe passage to the humidifier dew spray. ABSTRAKBilik sterilisasi didesain untuk mensterilisasi tubuh dengan menggunakan formulasi zat pengisi yang tidak berbahaya bagi permukaan kulit. Formulasi yaitu komposisi cairan pengisi (jenis, takaran dan jumlah) menggunakan zat yang aman bagi tubuh yang sesuai, tentu memberi manfaat. Penggunaan bilik sterilisasi menggunakan cairan pengisi yang benar dan aman. Bilik sterilisasi menggunakan mist nozzle sprayer (yang debitnya sesuai) untuk menyemprotkan cairan pengisinya sehingga pengguna aman. Bilik sterilisasi ini diberi nama "White Box". Penelitian "White Box"ini bertujuan merancang (fungsional dan struktural) dan menguji coba (uji fungsi dan uji kinerja) pada sebuah sistem dan mekanisme penyaluran pengembunan dari alat humidifier yang mampu memenuhi ruang bilik sterilisasi secara optimal. Metode rancang bangun bilik sterilisasi "White Box" menggunakan metode kualitatif dengan tahap kegiatan meliputi: (1) Tahap persiapan yaitu rancangan fungsional dan rancangan struktural"White Box"; (2) Tahap pelaksanaan yaitu analisa penggunaan alat dan bahan dan Pembuatan bilik sterilisasi; (3) Tahap Pasca Pelaksanaan yaitu pengujian bilik sterilisasi antara lain uji fungsi dan uji kinerja bilik sterilisasi. Muatan kegiatan rancang bangun bilik sterilisasi "White Box" dilakukan dengan cara menguji coba berbagai variasi prototipe, meliputi variasi dimensi pipa penyaluran, bentuk pipa penyalur, variasi sistem perpipaan. Proses validasi yang dilakukan meliputi: (1) Diamater pipa terhadap semburan embun humidifier; (2) Bentuk pipa penyalur terhadap semburan embun humidifier; dan (3) Panjang lintasan pipa terhadap semburan embun humidifier.